PENGARUH HARGA DAN FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN PEMESANAN AKOMODASI MELALUI ONLINE TRAVEL AGENT - Wikanatha Sagita, Putu Agus; Kusuma Negara, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p09, 2022)
This study aims to identify the effect of price and psychological factors on accommodation booking decisions through the Airbnb application. Data collection in this research was carried out by observation, interview, questionnaire and literature study techniques. The data analysis technique used is descriptive quantitative analysis and multiple linear regression analysis. The results of this study are expected to reveal whether tourists who book accommodation through Airbnb are merely motivated by the desire to get accommodation at a low price. Are psychological factors consisting of variables of motivation, perception, learning, and attitudes related to the desire of tourists to learn new things such as knowing the lives of local people also influence tourists in booking accommodation via Airbnb. The results of this study are independent variables consisting of price variables (X1), perception variables (X3), learning variables (X4), attitude variables (X5) significantly influence the dependent variable, namely the accommodation booking variable (Y). Whereas the motivation variable (X2) which is related to the trend indicator of the use of technology to book accommodations anywhere and anytime has no significant effect in booking accommodations through Airbnb's Online Travel Agent.